Redefining Strategic Management: - Sonia Taneja; Yasemin Atinc; Mildred Pryor (Journal of Accounting, Business and Management (JABM), 2023)
This article discusses strategic management from the perspectives of various experts in the area as well as from the perspectives of foundational strategic management theories and tools. Current issues are discussed which require strategists to expand their thinking about items which are relevant to the strategic management of their respective organizations. Part of this article is descriptive based on research relating to strategic management experts, theories, and tools. The rest of the article explains in detail the 5P's Leadership Model (which was created by one of the authors) so that it can be used by both academicians and organizational leaders. The 5Ps Strategic Leadership Model is introduced as complementary to many of the foundational theories of strategic management. It positively contributes to the strategic management academic discipline because it includes required organizational elements which must be aligned to ensure successful strategic management of an organization. We observe that the 5Ps Strategic Leadership Model positively contributes to the strategic management academic discipline and to the practitioners’ need for assistance in the execution of strategic plans.